Component Commonality with Service Level Requirements - Gerchak, Yigal; Magazine, Michael J.; Gamble, A. Bruce (Management Science, 1988)
This paper extends recent results of Baker et al. (Baker, K. R., M. J. Magazine, H. L. W. Nuttle. 1986. The effect of commonality on safety stocks in a simple inventory model. Management Sci. 32 982–988.) in understanding the impact of component commonality on stocking levels under service level constraints. A model is formulated for an arbitrary number of products with general joint demand distribution. The results obtained are not all intuitive. While utilizing commonality is beneficial, nothing general can be said about the resulting change in the components' stock levels. When the cost structure is of a particular simple form, though, some interesting general patterns do emerge. We also discuss the case of using a service-level measure where rationing of common components might be required, and characterize the implied rationing rule.